The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.31234/osf.io/ys6xz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reporting Racial and Ethnic Diversity in Eating Disorder Research Over the Past 20 Years

Abstract: Although there have been calls for better understanding the presentation of eating disorders in racially and ethnically diverse groups for the last two decades, recent increased attention to racial and ethnic disparities have again brought to light issues of diversity, equity, and inclusion. However, there is currently limited empirical information on racial and ethnic representation in eating disorders research, making it difficult to understand where improvements are needed. To address this gap, the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Slightly over half of the studies overall reported full race/ethnicity data, and a quarter reported none. Consistent with Egbert et al (2022), reporting of race/ethnicity data increased over time. Yet, 10% of studies published in the last decade did not report race or ethnicity and 20% reported only % White, non‐White, or minority.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Slightly over half of the studies overall reported full race/ethnicity data, and a quarter reported none. Consistent with Egbert et al (2022), reporting of race/ethnicity data increased over time. Yet, 10% of studies published in the last decade did not report race or ethnicity and 20% reported only % White, non‐White, or minority.…”
Section: Discussionsupporting
confidence: 83%
“…It is important to emphasize that best practices will continue to evolve over time, and researchers should update their methodology accordingly. Additionally, these recommendations are tailored toward US‐based researchers; we refer readers to Egbert et al (2022) for additional recommendations relevant to research conducted internationally and welcome dialogue from international experts and researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men and people of color are underrepresented in the ED literature and disparities in the prevention, assessment, and treatment of these conditions in these groups persist (Egbert et al, 2022; Goel, Thomas, et al, 2022, Murray et al, 2017). To optimize ED screening and detection, it is imperative that our most widely used measurement tools are validated within and across groups, and invariance is established to enhance confidence in the validity of score interpretations and comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to diversifying our workforce, we encourage scientists to commit to scholarship that benefits underserved populations and goes beyond understanding EDs using data from a homogenous population (e.g., young, White cisgender females from Westernized societies). Although EDs can affect anyone, regardless of race/ethnicity, gender, or cultural group (Cheng, Perko, Fuller‐Marashi, Gau, & Stice, 2019), and we know they do (e.g., Marques et al, 2011), historically marginalized racial/ethnic populations are less likely to be recruited, assessed, and retained in ED research (Egbert, Hunt, Williams, Burke, & Mathis, 2022; Goel, Thomas, Boutté, Kaur, & Mazzeo, 2021). When recruitment of diverse study participants is limited, study results become less generalizable to underrepresented groups, perpetuating the myth that EDs affect only young, White cisgender females from Westernized societies.…”
Section: Research: Accountability To Ensure Our Research Benefits Und...mentioning
confidence: 99%